2015
DOI: 10.3329/jbt.v9i1.22779
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Consumers’ Purchasing Decision of Toiletries Products: An Empirical Study on Square Toiletries in Khulna City

Abstract: This study is an attempt to identify the factors which affect consumers in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[9] In a research, Islam, M.R. [10] discovered that customers assess brand image, cost and obligations, distinctiveness, prestige, and customer relationship while making purchase decisions. A.B.…”
Section: P Venkata Subbaiah (2021)mentioning
confidence: 99%
“…[9] In a research, Islam, M.R. [10] discovered that customers assess brand image, cost and obligations, distinctiveness, prestige, and customer relationship while making purchase decisions. A.B.…”
Section: P Venkata Subbaiah (2021)mentioning
confidence: 99%
“…Conducting the study among 200 respondents study reveals some important factors influenced on customer's perception toward choosing branded clothes while purchasing and these are offers and discount, attractive range of color and designs, reasonable product price, the frequency of advertisement in print and electronic media and the attractiveness of advertisements. Islam et al(2014). Babu (2004) found that TV advertisement and celebrity endorsement attract customer m more to recall the message regarding the brand very rapidly and female consumers feel confident tsao buy the product when they catch positive word of mouth of the product.…”
Section: Literature Reviewmentioning
confidence: 99%